Resilience and Intergenerational Fairness in Collective Defined Contribution Pension Funds - Oskar Goecke (Technische Hochschule Köln, Institut für Versicherungswesen (ivwKöln), 2018)
A pension system is resilient if it able to absorb external (temporal) shocks and if it is able to adapt to (longterm) shifts of the socio-economic environment. Defined benefit (DB) and defined contribution pension plans behave contrastingly with respect to capital market shocks and shifts: while DB-plan benefits are not affected by external shocks they totally lack adaptability with respect to fundamental changes; DC-plans automatically adjust to a changing environment but any external shock has a direct impact on the (expected) pensions. By adding a collective component to DC-plans one can make these collective DC (CDC)-plans shock absorbing - at least to a certain degree. In our CDC pension model we build a collective reserve of assets that serves as a buffer to capital market shocks, e.g. stock market crashes. The idea is to transfer money from the collective reserve to the individual pension accounts whenever capital markets slump and to feed the collective reserve whenever capital market are booming. This mechanism is particular valuable for age cohorts that are close to retirement. It is clear that withdrawing assets from or adding assets to the collective reserve is essentially a transfer of assets between the age cohorts. In our near reality model we investigate the effect of stock market shocks and interest rate (and mortality) shifts on a CDC- pension system. We are particularly interested in the question, to what extend a CDC-pension system is actually able to absorb shocks and whether the intergenerational transfer of assets via the collective reserve can be regarded as fair.
urn:nbn:de:hbz:832-cos4-8049
Keywords: 330